Implementation of the advanced HIV disease package of care using a public health approach: lessons from Nigeria - Williams Eigege; Oche Agbaji; Nere Otubu; Opeyemi Abudiore; Oluwakemi Sowale; Boma Levy-Braide; Asari Inyang; Dinesh Rathakrishnan; Ikechukwu Amamilo; James Conroy; Folu Lufadeju; Carolyn Amole; et al. (BMC Public Health)
Abstract Background Nigeria adapted the WHO package of care for Advanced HIV Disease (AHD) in 2020. The package includes CD4 + cell count testing to identify People Living with HIV (PLHIV) with AHD, screening and treatment of opportunistic infections, rapid antiretrovirals (ART) initiation, and intensive adherence follow-up. The national program adopted a phased approach in the rollout of the AHD package of care to learn lessons from a few representative health facilities before scaling up across the country. This study describes the process and lessons learned from the first phase of implementation. Methods This was a prospective observational study, and participants were enrolled between February and September 2021. Healthcare-worker (HCW) capacity was built to implement the AHD package of care. The study population included newly diagnosed PLHIV ≥ 10 years presenting to care in 28 selected facilities across 4 states in Nigeria. Eligible participants received CD4 + cell testing at baseline. Those with CD4 + cell count < 200 cells/mm3 were subjected to a blood cryptococcal antigen (CrAg) test and urine TB lateral flow lipoarabinomannan (LF-LAM). Those with positive CrAg tests had a cerebrospinal fluid (CSF) test to confirm cryptococcal meningitis. Those negative for both blood CrAg and TB LF-LAM were rapidly initiated on ART and underwent intensive follow-up. Participants were followed up for 12 months. Results A total of 6,781 patients were enrolled; 71% (4,812) received CD4 + cell count test, of which 41% (1,969 of 4812) had a CD4 + count < 200 cells/mm3. Approximately 81% (1,492 of 1,850) of those with CD4 + count < 200 cells/mm3 had TB LF-LAM test results documented; 25% were positive, of which 47% started TB treatment. Blood CrAg screening coverage among those with CD4 + count < 200 cells/mm3 was 88% (1,634 of 1,850), of which 5% (85 of 1,634) were positive. Cotrimoxazole preventive therapy was initiated for 65% (1,198 of 1,850) of the participants with CD4 + count < 200 cells/mm3, and 70% (966 of 1,375) of AHD patients with a negative TB LF-LAM and blood CrAg results were initiated on ART on the day of enrolment. Approximately 91% (421 of 461) of those who received viral load results at month 12 post-enrollment were virally suppressed. The retention rate and the Kaplan Meier survival probability estimate at month 12 were 65% (1,204 of 1,850) and 0.93 (CI, 0.91–0.94), respectively, for the enrolled participants. Conclusion Implementation of the AHD package of care in Nigeria has improved the diagnosis of TB and CM, and will potentially enhance the quality of care for PLHIV if sustained. Findings from this implementation were used to guide national scale-up.